Smallholder farmers can achieve more sustainable wheat production through Consolidating Land for Uniform Practice - Ren, Taoyu; Yang, Xue; Zhang, Wushuai; Tang, Wenhui; Li, Yajuan; Tian, Yinghao; Ren, Jiawen; Yan, Jun; Guo, Xiaoxia; An, Zhichao; Zhang, Hongyan (Frontiers in Plant Science, 2025)
IntroductionLand fragmentation of smallholder agriculture significantly constrains the adoption rate of optimal management practices and sustainable crop production.MethodsWe developed and implemented an innovative management model known as Consolidating Land for Uniform Practice (CLUP), which aimed to foster multi-actor collaboration and facilitate the large-scale application of optimal practices without altering land ownership. CLUP was implemented in wheat fields in the North China Plain for three consecutive years.ResultsCompared to conventional farmers’ practices (FP), the CLUP approach improved wheat yield by 14%, nitrogen recovery efficiency by 35%, net ecosystem economic benefit by 86%, and agricultural labor productivity by 53%. Additionally, greenhouse gas (GHG) emissions per hectare and per ton of grain were reduced by 18% and 32%, respectively. Although the wheat yield and environmental performance of CLUP were not as good as that of scientist-led optimal practices (SP), its agricultural labor productivity was 60% higher, and its economic cost was 10% lower than SP.DiscussionThe CLUP model facilitates a transformative partnership by integrating the cutting-edge knowledge from universities, policy support from governments, and machinery services from enterprises, while emphasizing the participation of smallholder farmers. Overall, this study provides empirical evidence for optimizing agricultural practices and land management strategies, offering practical solutions for smallholder-dominated areas in the Global South.